Sistem Peramalan Produksi Jagung Provinsi Jawa Barat Menggunakan Metode Double Exponential Smoothing - Aris Purwanto; Siti Nurul Afiyah (Jurnal Ilmiah Teknologi Informasi Asia, 2020)
Corn (Zea mays) is one of the most important food-producing plants in the world, including in Indonesia specifically in the province of West Java. Corn plants can be made as raw materials for various pharmaceutical, cosmetic and chemical industrial products. Corn production in West Java Province during 1993-2015 changed the data trend. To find out the amount of corn production for the following year forecasting is needed, one of the methods that can be used to predict the case of data trend patterns using the double exponential refinement method. In this method we will make decisions according to the MAPE won that was obtained. In this study, MAPE was obtained at 9.38%, which means that the accuracy rate was 90.62% at alpha 0.4 with forecasting of corn production in West Java Province for the following year at 1049839.84 ft.